The outcome of surgical resection in complete paraplegia patient due to thoracic schwannoma - Maria Monica; Bair Ginting (Neurologico Spinale Medico Chirurgico, 2021)
Spinal schwannoma is the most common benign intradural spinal tumor. However, studies regarding the neurological outcome of tumor resection in complete paraplegia patients are still lacking. The authors report a case of complete paraplegia due to primary intradural extramedullary low-grade schwannoma of the spinal cord. Surgery was performed 5 weeks after the paraplegia complaint first occurred. The patient did not regain motor nor sensory function in the 1-month follow-up but resolution of pain was achieved. The patient was able to perform daily activity more comfortably. In the event of complete paraplegia, surgery should still be offered promptly as it can still benefit the patient. Possible factors that could have influenced the prognosis in our study are discussed.